(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
In the article the results of mineralogical, geochemical and genetic studies are presented which have been conducted in Phkhrut ore deposite of Zangezur ore region of RA. For the first time the molybdenite-chalcopyrite, quartz, quartz-pyrite, quartzcarbonate- base metal, quartz-arsenopyrite and quartz-carbonate-gypsum paragenetic mineral associations are described and vertical zonation of mineralization is revealed. All these types of ores are gold-bearing. In the ores gold is presented as own mineral (native gold, petzite, calaverite, krennerite) and isomorphic form in sulfides, particularly in pyrite. Along with gold Ag, Bi, Zn, Cu, Pb, Cd, Se, Te, Ge, Ga, in are interesting. The bulk of these elements form their own minerals, the other part in the form of isomorphic impurities are present in the sulfides and rock-forming minerals. By mineral composition, geochemical features and conditions of their formation, Phkhrut ores belong to quartz-gold sulfide formation.